The Relationship Between Maternal Education Level and Family Income on The Incidence of Stunting in Toddlers at The Madiun City Health Center - Nurwasilah, Nurwasilah; Sahadewa, Sukma; Andiani, Andiani (Universitas Pahlawan Tuanku Tambusai, 2024)
Stunting is a condition that occurs in toddlers who experience growth failure due to chronic malnutrition based on a z-score (TB/U) value of less than -2 SD (Standard Deviation). Stunting can be caused by a low level of maternal knowledge. Family income is also a risk factor for stunting. The purpose of this study was to analyze the relationship between maternal education level and family income on the incidence of stunting in toddlers at the Madiun City Health Center. This study used an analytical observational method with a case control design. The population in this study was all mothers who had toddlers in Madiun City. Respondents in this study consisted of 34 people, obtained from questionnaires with the total sampling method. The results of Chi-Square analysis showed that there was no relationship between maternal education level (p = 0.290), no relationship between family income level (p = 0.628), maternal education level and family income level (p = 0.545) greater than p value = 0.05; showed that there was no relationship between maternal education level and family income level with the incidence of stunting in toddlers at the Madiun City Health Center. There is no relationship between maternal education level and family income with the incidence of stunting in toddlers at the Madiun City Health Center.